Clinical profile of patients with obesity and COVID-19 in an outpatient setting in northeastern Brazil: a retrospective cohort study (Research, Society and Development, 2022)
Objective: To analyze the clinical profile of obese patients with COVID-19 in ambulatory care during the first wave of the pandemic. Methods: A retrospective observational study conducted in an outpatient setting in Aracaju/SE, Brazil. The patients with COVID-19 received medical care in a referral center from April to August 2020 and were followed remotely. Clinical data was analyzed using Jamovi 1.2.27. Results: Of 1,134 patients with COVID-19, 288 (25.4%) were obese, 59.7% were women. Hypertension, diabetes, dyslipidemia, and chronic kidney disease were more frequent in the obese group. Dyspnea and diarrhea were more frequent in obese individuals, while odynophagia, nausea, and vomiting were more common in non-obese individuals. Attending physicians prescribed more antibiotics, ivermectin, corticosteroids, and heparin for obese patients. Hospital admission (6.6% vs. 3.1%; p=0.008) and use of oxygen therapy (5.1% vs. 2.1%; p=0.011) were more frequent in the obesity group. Obesity was independently associated with hospital admission in multivariate analysis (OR: 2.561, 95% CI 1.352 - 4.853; p=0.004). The lethality rate was higher in obese individuals (2.1% vs. 0.7%; p=0.049). Conclusion: In this outpatient cohort of COVID-19 patients, there were more comorbidities among obese individuals. Despite the low frequency of unfavorable outcomes overall, obesity increased the risk of hospital admission and there were more deaths among patients with obesity.